Roads And Road Safety - Tashpulatova Gulzoda Kadyrovna; Amanov Zakir Charyevich (Zien Journals, 2022)
Based on the analysis, the main factors of the road infrastructure were determined, and measures aimed at increasing road safety were outlined
Keywords: motorization; level of motorization; road safety; traffic accidents